Effectiveness of Single-Visit Root Canal Treatment and Adhesive Restoration in Improving Accessibility of Tooth Preservation Services: A Case Report - Teuku Agus Surya; Widi Prasetia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Background: The management of teeth with pulp necrosis and symptomatic apical periodontitis requires effective root canal disinfection and durable restoration. Single-visit root canal therapy with bioceramic sealers and adhesive restorative techniques provides a comprehensive approach to promote periapical healing and tooth preservation. Aim: This case report describes the endodontic treatment and restorative management of a maxillary second premolar with a periapical lesion using single-visit endodontic and DME technique for direct composite restoration. Case Report: A patient presented with pain during chewing on the maxillary left second premolar, previously restored one year earlier. The tooth was initially sensitive but developed pain on mastication after six months. Clinical findings included negative thermal response, positive percussion, negative palpation, and no mobility. Radiographs showed a periapical lesion. The diagnosis was pulp necrosis with symptomatic apical periodontitis. Case Management: Endodontic treatment was performed in a single visit. Root canal preparation was followed by obturation using a single-cone technique with bioceramic sealer. Restorative management involved the DME technique to elevate the cervical margin, followed by direct composite for functional restoration. Discussion: Single-visit root canal therapy provides outcomes comparable to multi-visit protocols. Bioceramic sealer enhances periapical healing due to its bioactivity and sealing properties. The DME technique facilitates restorative access and margin control in deep areas, while direct composite ensures conservative reinforcement and esthetics. Conclusion: This integrated single-visit approach combining bioceramic obturation, DME, and direct composite restoration achieved successful management of a maxillary second premolar with pulp necrosis and.